Enrichment of cornstarch with curcumin and vitamin D3 coencapsulated in lyophilized liposomes using high shear wet agglomeration - Chaves, Matheus Andrade (2021)
Nowadays, the increasingly search for healthier foods is a recurrent practice by consumers. Therefore, there is a continuous to develop new technologies for the controlled release of bioactives in food formulations. Curcumin is the main compound extracted from turmeric plant with well-known antioxidant, anti-inflammatory and antimicrobial properties that has been used in food industry as a spice, preservative, and natural colorant. Vitamin D3 (cholecalciferol) is a liposoluble prohormone molecule with a key role in the health of teeth and bones, since its intake promotes an increase in the absorption of calcium by the blood. Despite their benefits, the incorporation of curcumin and vitamin D3 into aqueous-based food formulations can be hindered by their high hydrophobicity. Such problem can be overcome by encapsulating both bioactives into lipid carriers as liposomes. Liposomes have high biocompatibility with epithelium cells, as well as low toxicity. From an industrial viewpoint, the production of liposomes using the hydration of proliposomes method appears as an easily scalable process and presents several advantages over the other methods discussed in literature such as lower cost and the need for no organic solvents other than ethanol for manufacturing. Alternatively, supercritical methods to produce liposomes are environmentally friendly and result in high encapsulation efficiencies. The main objective of this work was to produce a new enriched cornstarch containing curcumin and vitamin D3 coencapsulated in lyophilized liposomes using a high shear wet agglomeration method. This technique is widely used for the production of powders with improved flowability properties. Lyophilized vesicles were prepared using two phospholipids, soybean hydrogenated Phospholipon 90H and fat-free unpurified Lipoid S40. To this purpose, the feasibility for the production of proliposomes and liposome dispersions using different phospholipid ratios was first tested. Proliposomes were characterized using methods often used for food powders, whereas methods used for colloidal suspensions were applied to characterize the liposome dispersions. These liquid dispersions were lyophilized and the resulted powders also characterized. At last, the lyophilized vesicles were blended to commercial cornstarch using maltodextrin as liquid binder and high shear wet agglomeration as the main process. Overall, all systems herein proposed were suitable for the retention of curcumin and vitamin D3 over the storage time. Phospholipid ratio proved to have the major influence on physicochemical parameters of carriers. Cornstarch samples presented improved technological and handling properties and retained up to 96.7% of curcumin and 98.2% of vitamin D3 after 30 days of storage. This work provided an innovative and potential purpose for a simple and widespread process as high shear wet agglomeration and allowed to develop a new functional product with high-added value using low-cost ingredients.